1997
DOI: 10.1037/0882-7974.12.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Everyday activity parameters and competence in older adults.

Abstract: Parameters of everyday activities in relation to cognitive, social, and emotional competence were examined in 2 studies. The parameters included frequency, difficulty, importance, intentions for future activities, changes in past activities, and ability of performance. The challenge hypothesis, in which performance of optional activities experienced as moderately difficult is associated with greatest well-being, was also tested. Two samples of older adults completed a life history interview and measures of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…This apparent sensitivity of the activity measure to social context does not make it a poor indicator of competence. Rather, it further illustrates the argument [8,14,16] that competence is fundamentally the ability to adapt to age-related changes in the availability of internal and external resources, including, in this case, the availability of greater leisure time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This apparent sensitivity of the activity measure to social context does not make it a poor indicator of competence. Rather, it further illustrates the argument [8,14,16] that competence is fundamentally the ability to adapt to age-related changes in the availability of internal and external resources, including, in this case, the availability of greater leisure time.…”
Section: Discussionmentioning
confidence: 99%
“…The interview, adapted from Pushkar et al [14], asked about activities in eleven domains: meal preparation, housekeeping/home maintenance, grocery shopping, financial management, visiting family and friends, entertaining family and friends, physical activities, hobbies, clubs and organizations, volunteering, and traveling. For each domain, the participants compared their current level of engagement with their engagement in it, when they were about age 50 years.…”
Section: Competence Measurementioning
confidence: 99%
See 1 more Smart Citation
“…The retirement literature has indicated many ways in which individuals try to achieve this continuity. For example, retirees may view retirement as another logical career stage (Quick & Moen, 1998); keep a similar life routine or schedule as before (Kim & Feldman, 2000); participate in activities and sustain levels of social contact (Harlow & Cantor, 1996;Pushkar, Arbuckle, Conway, Chaikelson, & Maag, 1997); maintain stable self-concept (Troll & Skaff, 1997); or continue to work (Kim & Feldman, 2000). Generally, retirees try to maintain the same personal goals and lifestyle they had before retirement (Richardson & Kilty, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One approach involves ratings of the degree of commitment or importance attributed to one's activity participation; studies have consistently demonstrated positive relationships with subjective well-being (Pushkar, Arbuckle, Conway, Chaikelson, & Maag, 1997;Ray & Heppe, 1986). Another approach to quantifying meaning measures the level of satisfaction individuals ascribe to their activity involvement.…”
mentioning
confidence: 99%